A comparative study of naturally and synthetically derived bioceramics for biomedical applications. (2020) - Mathina, M.; Shinyjoy, E.; Kavitha, L.; Manoravi, P.; Gopi, D.
Abstract: Hydroxyapatite (HAp) is a bioactive material, similar to the mineral constituent of natural bone and teeth. Naturally derived HAp is currently used in various types of orthopedic and maxillofacial applications because of their osteoconductive properties and tissue responses. In recent years, the use of natural biogenic structures and materials for medical purpose has been motivated by limitations in producing synthetic materials. Our study mainly focused to synthesis of hydroxyapatite from biogenic waste (squid pens) material. Naturally derived HAp can develop a tight bond with bone tissue, which is stable towards bio resorption and has no adverse effects on the human body. For these reasons the scope of the present work is focused on the synthesis of HAp derived from biogenic waste for biomedical applications. Our results showed that biogenic HAp is non-toxic and improve the cell adhesion. All the as-synthesized sample were investigated by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM) and Energy dispersive X-ray analysis (EDAX).